Revolutionising food advertising monitoring: a machine learning-based method for automated classification of food videos - Michele Bittencourt Rodrigues; Victória Pedrazzoli Ferreira; Rafael Moreira Claro; Ana Paula Bortoletto Martins; Sandra Avila; Paula Martins Horta (Cambridge University Press, 2023)
Abstract Objective: Food advertising is an important determinant of unhealthy eating. However, analysing a large number of advertisements (ads) to distinguish between food and non-food content is a challenging task. This study aims to develop a machine learning-based method to automatically identify and classify food and non-food ad videos. Design: Methodological study to develop an algorithm model that prioritises both accuracy and efficiency in monitoring and classifying advertising videos. Setting: From a collection of Brazilian television (TV) ads data, we created a database and split it into three sub-databases (i.e. training, validation and test) by extracting frames from ads. Subsequently, the training database was classified using the EfficientNet neural network. The best models and data-balancing strategies were investigated using the validation database. Finally, the test database was used to apply the best model and strategy, and results were verified with field experts. Participants: The study used 2124 recorded Brazilian TV programming hours from 2018 to 2020. It included 703 food ads and over 20 000 non-food ads, following the protocol developed by the INFORMAS network for monitoring food marketing on TV. Results: The results showed that the EfficientNet neural network associated with the balanced batches strategy achieved an overall accuracy of 90·5 % on the test database, which represents a reduction of 99·9 % of the time spent on identifying and classifying ads. Conclusions: The method studied represents a promising approach for differentiating food and non-food-related video within monitoring food marketing, which has significant practical implications for researchers, public health policymakers, and regulatory bodies.